2021
DOI: 10.3389/fped.2021.607285
|View full text |Cite
|
Sign up to set email alerts
|

Children With Inflammatory Bowel Disease in the COVID-19 Main Endemic Focus: The Lombardy Experience

Abstract: Objectives: In the era of Coronavirus 2019 (COVID-19), concern has been raised for immunosuppressed patients, including children with inflammatory bowel diseases (IBD). We aimed to collect data from IBD tertiary centers of Lombardy during pandemic.Methods: A cross-sectional survey enrolling IBD children has been completed by seven major IBD centers in Lombardy during lockdown. The clinical form included questions on any symptom consistent with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The main source of SARS-CoV-2 infection in our patient group was close contact with a SARS-CoV-2 PCR-positive patient. Similar findings were reported in previous studies; Yuksel et al [ 10 ] reported that among patients liver transplant recipients, the main source of infection was parents/siblings, and Sansotta et al [ 9 ] reported that among patients with inflammatory bowel disease, the source of infection was close contact with a positive patient. It is important to inform patients with chronic disease in close contact with a positive patient about the virus transmission risk.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The main source of SARS-CoV-2 infection in our patient group was close contact with a SARS-CoV-2 PCR-positive patient. Similar findings were reported in previous studies; Yuksel et al [ 10 ] reported that among patients liver transplant recipients, the main source of infection was parents/siblings, and Sansotta et al [ 9 ] reported that among patients with inflammatory bowel disease, the source of infection was close contact with a positive patient. It is important to inform patients with chronic disease in close contact with a positive patient about the virus transmission risk.…”
Section: Discussionsupporting
confidence: 88%
“…Literature on the clinical features and outcomes of SARS-CoV-2 infection in children with chronic gastrointestinal and liver diseases has mainly focused on three diseases: CLD, liver transplantation recipients, and inflammatory bowel disease [ 8 9 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be consistent with other studies, showing good adherence to biological treatments ( 21 24 ) and in this unprecedented context, in comparison to patients with other chronic non-respiratory pathologies treated with immunosuppressors, JIA patients seems to be compliant with their treatment. In fact, children with inflammatory bowel disease did not discontinue their immunomodulatory treatments ( 25 ), patients with rheumatoid arthritis declared a modification in their treatment in 11% of cases ( 26 ), and patients with systemic lupus modified their treatment in 10% of cases ( 27 ). Of course, these data must take into account the self-report aspect of our study and the difficulty of measuring therapy adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sansotta et al [ 34 ] highlights that, although all patients were instructed to continue therapy, none had a severe course and there were no cases of hospitalization. During this period, two patients experienced fever and gastrointestinal symptoms.…”
Section: Inflammatory Bowel Diseases Covid-19 and Childrenmentioning
confidence: 99%